Novel Porcine Retina Cultivation Techniques Provide Improved Photoreceptor Preservation - Wagner, Natalie; Reinehr, Sabrina; Gammel, Maurice R.; Greulich, Andrea; Hurst, José; Dick, H. Burkhard; Schnichels, Sven; Joachim, Stephanie C. (Frontiers in Neuroscience, 2020)
Age-related macular degeneration (AMD) is the leading cause of blindness in industrialized countries among people over 60 years. It has multiple triggers and risk factors, but despite intense research efforts its pathomechanisms are currently not completely understood. AMD pathogenesis is characterized by soft drusen in Bruch’s membrane and involves the retinal pigment epithelium-Bruch’s membrane-choroid-complex and adjacent structures, like photoreceptors. This study explores the potential of novel cultivation techniques to preserve photoreceptors in retinal explants to gain better insights in AMD pathology. The porcine retina explants were cultured for four and eight days, using three different explantation techniques, namely control (photoreceptors facing down, touching the filter), filter (photoreceptors facing up, turned sample using a filter), and tweezers (photoreceptors facing up, turned sample using tweezers). Optical coherence tomography revealed that the tweezers method had the best capacity to limit thinning of the retinal explants. Both novel methods displayed advantages in maintaining outer segment thickness. Additionally, immunofluorescence evaluation revealed a better preservation of opsin+ cells and rhodopsin signal intensity in both novel methods, especially the tweezers method. Furthermore, RT-qPCR analysis demonstrated an upregulation of OPSIN and RHODOPSIN mRNA expression in tweezer samples at eight days. Amacrine and bipolar cell numbers were not altered at day four of cultivation, while a cultivation until eight days led to reduced bipolar cells. At four days, CALRETININ mRNA was upregulated in filter samples, but PKCα expression was downregulated. Retinal ganglion cells were diminished in both novel techniques, due to a direct physical contact with the insert. Remarkably, no difference in TUBB3 mRNA expression was detected amongst the techniques. Nevertheless, both novel methods exhibited an improved retention of photoreceptor cells. In conclusion, the tweezers technique was the most promising one. Due to the high homology of the porcine to the human retina it provides a reasonable alternative to in vivo rodent models. Consequently, an adapted co-culture system based on the current findings may serve as an ex vivo model suitable to analyze AMD pathomechanisms and novel therapeutic approaches.